EFFECTIVENESS ON DROP TRAILER METHOD (DTM) OF HAULAGE INDUSTRY IN MALAYSIA - Melan, Mustakim; Md Zahid, Mazlan; Sabar, Rohafiz (International Journal of Supply Chain Management, 2019)
This paper focuses on the customersâ?? commitment and behaviour towards an effective of â??drop trailer methodâ?? (DTM) in haulage industry. There was limited study in customersâ?? commitment and behaviour on the efficiency of DTM. The study on DTM was due to the increasing volumes of international trade using haulage transport and trailers which led to rapid growth of container volumes at Malaysian ports. The maximum usage of trailers are needed to cater the growth of containersâ?? movements at present. The detention trailers by the customers during loading and unloading processes caused inefficiency in haulage performance. Therefore, monitoring on the usage of trailers will increase to the overall movements and reduction in the detention times. Exploratory and qualitative studies are also used in this research. The results indicated that the effectiveness of DTM is a crucial part to benchmark on the overall businesses, particularly in effective ways coordinating and utilising to the overall trailers. It is used to indicate haulage operatorsâ?? achievement towards their objectives. The better control in DTM may be used for better planning in the movements in future. The study suggests on the effective DTM structure for better impact in monitoring haulage business towards costs, revenues and profits.